Severe excessive daytime sleepiness induced by hydroxyurea. (24th January 2017) - Revol, Bruno; Joyeux‐Faure, Marie; Albahary, Marie‐Victoire; Gressin, Remy; Mallaret, Michel; Pepin, Jean‐Louis; Launois, Sandrine H.
Abstract: Excessive daytime sleepiness (EDS) has been reported with many drugs, either as an extension of a hypnotic effect (e.g. central nervous system depressants) or as an idiosyncratic response of the patient. Here, we report unexpected and severe subjective and objective EDS induced by hydroxyurea therapy, with a favorable outcome after withdrawal. Clinical history, sleep log, polysomnography, and multiple sleep latency tests confirming the absence of other EDS causes are presented.